Kashmiri life narratives : human rights, pleasure and the local cosmopolitan - Rizwan, Rakhshan (New York, NY : Routledge, 2020)
Kashmiri Life Narratives takes as its central focus writings -- memoirs, non-fictional and fictional Bildungsromane -- published circa 2008 by Kashmiris/Indians living in the Valley of Kashmir, India or in the diaspora. It offers a new perspective on these works by analyzing them within the framework of human rights discourse and advocacy. Literature has been an important medium for promoting the rights of marginalized Kashmiri subjects within Indian-occupied Kashmir and that it has been successful in putting Kashmir back on the global map and in shifting discussion about Kashmir from the political board rooms to the international English-language book market. In discussing human rights advocacy through literature, this book also effects a radical change of perspective by highlighting positive rights (to enjoy certain things) rather than negative ones (to be spared certain things). Kashmiri life narratives deploy a language of pleasure rather than of physical pain to represent the state of having and losing rights.
Introduction: The Poet and the Cassette Player Chapter 1 Mobilizing Pleasure through Genre: Curfewed Night and Our Moon Has Bloodclots as Kashmiri BildungsromaneChapter 2 Literary Fiction as an Alternative to a Human Rights Report: The Case of Mirza Waheed's The Collaborator Chapter 3 Imagining Local Cosmopolitanism and Cultural Human Rights in Sudha Koul's The Tiger Ladies Chapter 4 Palatable Fictions: Negotiating Narratives of Consumption and Subalternity in Jaspreet Singh's Chef Chapter Five Portable Pleasures and Papier Mache: Strategic exoticism in Mirza Waheed's The Book of Gold LeavesConclusion
OCLC-licensed vendor bibliographic record.
Keywords: Kashmiri literature -- History and criticism -- 21st century